The Effect of Inventory Intensity, Capital Intensity and Company Size on Tax Aggressiveness in Chemical Companies Listed on the IDX 2018-2022 - Aini Salsabila Firman; Pedi Riswandi; Winny Lian Seventeen; Foluke Nike Bolu-Steve (Sharia Economic and Management Business Journal (SEMBJ), 2024)
This final project research about the impact of the supply intensity, capital intensity and size of the company on the tax aggressiveness of the chemical company registered with the Indonesian stock exchange in 2018-2022. In this research, researchers use an independent variable that are: Supply intensity, capital intensity and company size. Whereas the dependent variables is: tax aggressiveness. The method of data analysis used in this research is the T test using the SPSS program. Where the results of this research show the intensity of supply and the intensity of capital have a significant impact on tax aggressiveness. While size of the company doesn't have impact of tax aggressiveness.